Символ и симулякр. Концепция символа в социологии постмодерна - Бурлачук, В.; Танчер, В. (Социология: теория, методы, маркетинг, 2004)
In sociology of postmodern, due to concepts of symbol and simulacra, one could reveal the phenomenon of total semiotic organization of social life. In the modern culture, determination without an object for determination gained the status of unique and self-sufficient reality. The modern culture loses feeling of life and reality. Language as a way of understanding got rid of the reality, life became a sign. The culture of postmodern denied the reality by changing it into an aspect of semiotics.